Explore structural and functional brain changes in insomnia disorder: A PRISMA-compliant whole brain ALE meta-analysis for multimodal MRI. Issue 14 (April 2020) - Wu, Yangyang; Zhuang, Yuan; Qi, Jun
Abstract : Abstract: Inconsistent results for comparison between insomnia disorder (ID) patients and healthy controls (HC) were obtained from previous neuroimaging studies. An activation likelihood estimation (ALE) meta-analysis was made for multimodal neuroimaging in ID. ALE analysis indicated that ID patients showed significant gray matter reductions in the right middle frontal gyrus (MFG), compared to HC. Regarding positron emission tomography studies, ALE analysis showed reduced relative cerebral glucose metabolism in the right amygdala, the right anterior cingulate cortex (ACC), and the right posterior cingulate gyrus (PCG) in ID patients, compared to HC. Regarding diffusion tensor imaging studies, the present study indicated that ID patients showed reduced fractional anisotropy values in the left putamen and the right caudate body, compared to HC. Additionally, ID patients showed reduced amplitude of low frequency fluctuations (ALFF) in the left fusiform gyrus (FG), the left middle temporal gyrus (MTG), the right MTG, the right anterior lobe (AL), and the left PCG, compared to HC. ID patients showed increased ALFF in the left MFG, compared to HC. ID patients showed reduced regional homogeneity (ReHo) in the left parahippocampal gyrus, the left sublobar, the left cuneus, the left precentral gyrus (PCG), the right AL, the right ACC, and the right PCG, compared to HC. ID patients showed increased ReHo in the left FG, the left precuneus, and the right cingulate gyrus, compared to HC. Moreover, the ALE analysis showed hypoactivation relative to HC in the left superior temporal gyrus (STG), the left MTG, the right inferior frontal gyrus, the right cuneus, and the right STG in ID patients. Via this ALE meta-analysis, we obtained these key regions suffering from deficits in ID. Abstract : Supplemental Digital Content is available in the text